1994
DOI: 10.2307/1939614
|View full text |Cite
|
Sign up to set email alerts
|

Higher Order Interactions in Ecological Communities: What Are They and How Can They be Detected?

Abstract: The detection and significance of higher order interactions (HOis) between species has been a matter of debate and experimentation in community ecology for several decades. HOis are considered potentially significant because their presence is assumed to mean that the dynamic behavior of a full community of species is unpredictable based on observations of interactions between subsets of the species within the community. Despite such attention, the causal mechanisms that produce HOis have been inadequately disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
383
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(389 citation statements)
references
References 21 publications
(83 reference statements)
5
383
0
1
Order By: Relevance
“…There are usually many possible direct and indirect interactions that can produce similar net effects on the abundance of a focal species (e.g., Adler and Morris 1994;Billick and Case 1994;Wootton 1994). We attempted to gain insight into the possible mechanisms for the treatment effects by measuring some of the processes directly affecting the biomass of herbivores and algae in the enclosures, namely the rates of predation on herbivores and the rates of dispersal into and out of the enclosures.…”
Section: Mechanisms For Effects Of Predator and Nutrientsmentioning
confidence: 99%
“…There are usually many possible direct and indirect interactions that can produce similar net effects on the abundance of a focal species (e.g., Adler and Morris 1994;Billick and Case 1994;Wootton 1994). We attempted to gain insight into the possible mechanisms for the treatment effects by measuring some of the processes directly affecting the biomass of herbivores and algae in the enclosures, namely the rates of predation on herbivores and the rates of dispersal into and out of the enclosures.…”
Section: Mechanisms For Effects Of Predator and Nutrientsmentioning
confidence: 99%
“…Traditionally, this question has been approached by decomposing food web complexity into more manageable subsets of interacting species, which are then studied in isolation from the rest of the community (Vandermeer, 1969;Billick and Case, 1994). This approach has shown that there are frequently emergent properties that arise only in the presence of multiple species (Sih et al, 1998;Strauss and Irwin, 2004) resulting in ecological and evolutionary outcomes that could not be predicted by on the basis of single-or even two-species dynamics (Iwao and Rausher, 1997;Strauss and Irwin, 2004;Thompson, 2005;Berenbaum and Zangerl, 2006;Parchman and Benkman, 2008;.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, much attention has been given to indirect effects in ecosystem processes [for instance, see Lawlor (1979), Strauss (1991), Billick and Case (1994), Menge (1995), Abrams and others (1996), and Rosemond (1996)]. For example, Menge (1995) identified 83 subtypes of indirect effects in a rocky intertidal community and found that they accounted for about 40% of the change in community structure.…”
Section: Indirect Effectsmentioning
confidence: 99%
“…For example, Menge (1995) identified 83 subtypes of indirect effects in a rocky intertidal community and found that they accounted for about 40% of the change in community structure. Billick and Case (1994) distinguished between higher-order interactions and indirect effects, identifying three types of higher-order interactions and two definitions of indirect effects. Abrams (1991) proposed a distinction between short-term and long-term indirect effects.…”
Section: Indirect Effectsmentioning
confidence: 99%